1995
DOI: 10.1017/s0021900200103146
|View full text |Cite
|
Sign up to set email alerts
|

Minification processes with discrete marginals

Abstract: We investigate the stationarity of minification processes when the marginal is a discrete distribution. There is a close relationship between the problem considered by Arnold and Isaacson (1976) and the stationarity in minification processes. We give a necessary and sufficient condition for a discrete distribution to be the marginal of a stationary minification process. Members of the Poisson and negative binomial families can be the marginals of stationary minification processes. The geometric minification pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Alternative integer-valued processes based on non-additive innovation through maximum and minimum operations were proposed by Littlejohn (1992), Littlejohn (1996), Kalamkar (1995), Scotto et al (2016), and Aleksić and Ristić (2021). For the count processes {X t } t∈N considered in these works, a certain nonlinearity is induced in the sense that the conditional expectation E(X t |X t−1 ) is non-linear on X t−1 (and also the conditional variance) in contrast with (3).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative integer-valued processes based on non-additive innovation through maximum and minimum operations were proposed by Littlejohn (1992), Littlejohn (1996), Kalamkar (1995), Scotto et al (2016), and Aleksić and Ristić (2021). For the count processes {X t } t∈N considered in these works, a certain nonlinearity is induced in the sense that the conditional expectation E(X t |X t−1 ) is non-linear on X t−1 (and also the conditional variance) in contrast with (3).…”
Section: Introductionmentioning
confidence: 99%
“…where the set of natural numbers N also includes zero. The discrete minification model, as an extension to the continuous minification model, has been proposed and studied to model count data for many years; see Lewis & Mckenzie (1991), Littlejohn (1992), Kalamkar (1995) This paper is organised as follows. Section 2 proposes a new min-INAR(1) process driven by explanatory variables and studies its basic properties.…”
Section: Introductionmentioning
confidence: 99%
“…random variables with the following probability mass function (pmf)PrGi=x=αxfalse(1+αfalse)x+1,xN,where the set of natural numbers double-struckN also includes zero. The discrete minification model, as an extension to the continuous minification model, has been proposed and studied to model count data for many years; see Lewis & Mckenzie (1991), Littlejohn (1992), Kalamkar (1995), among others. Aleksić & Ristić (2021) indicated that both the max‐INAR and min‐INAR models can account for the time series with extreme counts.…”
Section: Introductionmentioning
confidence: 99%